Evolution of Renewable Energy Research 2000–2026: A Bibliometric Exploration of Hot Topics and Knowledge Networks - Judijanto, Loso; Karnoto, Karnoto; Handoko, Susatyo; Risdwiyanto, Andriya; Irjanto, Bambang (Westscience Press, 2026)
This study aims to examine the evolution of renewable energy research from 2000 to 2026 using a bibliometric approach to identify key trends, emerging topics, and the intellectual structure of the field. Data were collected from the Scopus database and analyzed using VOSviewer to generate co-occurrence, overlay, and density visualizations. The results reveal a substantial increase in publication output over time, indicating growing global attention to renewable energy as a response to climate change and sustainability challenges. Keyword co-occurrence analysis shows that renewable energy research is structured around several major themes, including energy systems and policy, hydrogen production technologies, and electrochemical processes such as water splitting and hydrogen evolution reactions. Overlay visualization indicates a shift toward emerging topics such as machine learning, optimization, and energy system integration, reflecting the increasing role of digital technologies in enhancing energy efficiency. Density analysis further highlights the dominance of hydrogen-related research as a core hotspot within the field. Overall, the findings suggest that renewable energy research is becoming increasingly interdisciplinary, integrating engineering, environmental science, and data-driven approaches. This study contributes to a comprehensive understanding of the development and future direction of renewable energy research, providing valuable insights for researchers, policymakers, and practitioners in advancing sustainable energy transitions.